DIlp7-Producing Neurons Regulate Insulin-Producing Cells in Drosophila - Prince, Elodie; Kretzschmar, Jenny; Trautenberg, Laura C.; Broschk, Susanne; Brankatschk, Marko (Frontiers in Physiology, 2021)
Cellular Insulin signalling shows a remarkable high molecular and functional conservation. Insulin-producing cells respond directly to nutritional cues in circulation and receive modulatory input from connected neuronal networks. Neuronal control integrates a wide range of variables including dietary change or environmental temperature. Although it is shown that neuronal input is sufficient to regulate Insulin-producing cells, the physiological relevance of this network remains elusive. In Drosophila melanogaster, Insulin-like peptide7-producing neurons are wired with Insulin-producing cells. We found that the former cells regulate the latter to facilitate larval development at high temperatures, and to regulate systemic Insulin signaling in adults feeding on calorie-rich food lacking dietary yeast. Our results demonstrate a role for neuronal innervation of Insulin-producing cells important for fruit flies to survive unfavourable environmental conditions.